2021
DOI: 10.1021/acs.est.1c01288
|View full text |Cite
|
Sign up to set email alerts
|

Phase Saturation Control on Mixing-Driven Reactions in 3D Porous Media

Abstract: Transported chemical reactions in unsaturated porous media are relevant to environmental and industrial applications. Continuum scale models are based on equivalent parameters derived from analogy with saturated conditions and cannot appropriately account for incomplete mixing. It is also unclear how the third dimension controls mixing and reactions. We obtain three-dimensional (3D) images by magnetic resonance imaging using an immiscible nonwetting liquid as a second phase and a fast irreversible bimolecular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 85 publications
4
10
0
Order By: Relevance
“…Similar air cluster size distributions (Iglauer et al 2010(Iglauer et al , 2012Scheffer et al 2021) and a similar flow structure, displaying a clear separation of liquid flow in stagnation regions and preferential paths (Holzner et al 2015), have also been described in three-dimensional conditions. It has also been shown previously that the mixing dynamics in 3D unsaturated porous media follow the same scaling laws as in 2D unsaturated flows (Markale et al 2021). Therefore, we expect the adsorption mechanisms we describe for these 2D flow structures to remain valid for 3D conditions.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Similar air cluster size distributions (Iglauer et al 2010(Iglauer et al , 2012Scheffer et al 2021) and a similar flow structure, displaying a clear separation of liquid flow in stagnation regions and preferential paths (Holzner et al 2015), have also been described in three-dimensional conditions. It has also been shown previously that the mixing dynamics in 3D unsaturated porous media follow the same scaling laws as in 2D unsaturated flows (Markale et al 2021). Therefore, we expect the adsorption mechanisms we describe for these 2D flow structures to remain valid for 3D conditions.…”
Section: Discussionsupporting
confidence: 74%
“…It has also been shown previously that the mixing dynamics in 3D unsaturated porous media follow the same scaling laws as in 2D unsaturated flows (Markale et al. 2021 ). Therefore, we expect the adsorption mechanisms we describe for these 2D flow structures to remain valid for 3D conditions.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This revealed that the presence of biofilm increases the fluid flow velocity heterogeneity and the spreading of a transported solute . Furthermore, in abiotic porous media, the mosaic of high and low velocities within porous media enhances the reactivity, due to the enhanced creation of concentration gradients. , Despite these advances, the temporal evolution of the permeability field within porous media during bioclogging, its relation with the aggregation process of biofilm clusters, and its dependency on pore size and flow rate have remained largely unknown.…”
Section: Introductionmentioning
confidence: 99%